Densidad de la masa ósea y marcadores bioquímicos del metabolismo óseo: estudio transversal en adultos residentes de Lima Metropolitana, Perú - Garmendia-Lorena, Fausto (2020)
Objectives. To determine and correlate the bone mineral density (BMD) and the biochemical markers of bone metabolism in adults 30 to 40 years old from Lima, Perú, in year 2018. Methods. A total of 84 women and 53 men, 30 to 40 years old from Lima, Perú, were submmited to a descriptive, transversal study. They did not have symptoms nor treatment for bone metabolic diseases. Information about their present health state, personal and familiar physiological and pathological history and physical examinatión were registered. BMD was measured by dual energy-X-ray absorptiometry in spine, hip and forearm. Parathormone, osteocalcine, 25-hidroxi-vitamine-D, luteinizing hormone, estradiol in women, testosterone in men, calcium, phosphorus, alkaline fosfatase, total and fractionated proteins, creatinine were measured in blood; in urine N-telopéptide, calcium and phosphorus by conventional methods. Results. BMD was measured in 62 women and 40 males; 2 women and 1 man had osteoporosis and 3 women and 2 men osteopenia, who were taken out of statistical evaluation; 58 women and 35 men showed a normal BMD. Male subjects had a greater BMD, higher calcium, alkaline fosfatase and creatine blood concentrations than the female ones; 14 women y 2 men had low 25-OHvitaminaD concentrations. A positive correlation between the BMD and BMI was found. Conclusions. The normal BMD of persons 30 to 40 years old showed a linear figure and there was a positive correlate with the BMI; premature osteoporosis in 2 women and 1 men as well as osteopenia in 3 women y 2 men was found, low concentrations of 25-hidroxi-vitamine-D was detected in 16 persons.